The Urgency of Diagnostic Assessment in Improving the Quality of Learning in Islamic Religious Education - Evi Sulfaningsih; Tasman Hamami; Nurhidayat Nurhidayat; Siti Sahra; Retno Try Purnawati (AR-RASYID : Jurnal Pendidikan Agama Islam, 2026)
This study aims to analyze the urgency of diagnostic assessment in improving the quality of Islamic Religious Education (PAI) learning. The background of this research lies in the low quality of PAI learning, which remains predominantly cognitive-oriented while neglecting the integration of knowledge, religious attitudes, and worship skills. This study employed a library research method with content analysis using the Miles Huberman interactive model. The findings reveal four main urgencies of diagnostic assessment. First, it supports differentiated learning by mapping students’ initial abilities. Second, it provides the foundation for remediation and enrichment according to learners’ needs. Third, it increases learning motivation by aligning instruction with students’ conditions. Fourth, it fosters Islamic character formation through the integration of cognitive and non-cognitive. These results affirm that diagnostic assessment is not merely a technical tool but a fundamental strategy to achieve national education goals and support the implementation of the Merdeka Curriculum.